Champagne Prototyping: A Research Technique for Early Evaluation of Complex End-User Programming Systems - Blackwell, Alan; Burnett, Margaret; Peyton Jones, Simon (IEEE Symposium on Visual Languages and Human Centric Computing (VLHCC), 2004)
Although a variety of evaluation techniques are available to researchers of visual and end-user programming systems, they are primarily suited to evaluation of research systems. It is important to have evaluation techniques suitable for real-world programming environments, in order to satisfy realworld product managers of the usefulness of proposed new features. To help fill this gap, we present a new evaluation technique, based in part on Cognitive Dimensions and Attention Investment, called "Champagne Prototyping". The technique is an early-evaluation technique that is inexpensive to do, yet features the credibility that comes from being based on the real commercial environment of interest, and from working with real users of the environment. If you are interested in this paper, you may also be interested in our earlier paper "A user-centred approach to functions in Excel"; and in the European Spreadsheet Risk Interest Group (EuSpRIG).